Ефекти УФ-випромінювання на спіральне закручування у холестеричних системах, що містять фоточутливі азокси-нематики - Serbina, M.I.; Kasian, N.A.; Lisetski, L.N. (Publishing house "Academperiodika", 2012)
For cholesteric liquid crystal systems containing photosensitive nematic ZhK-440 and a mixture of cholesterol derivatives, the changes in helical twisting induced by UV radiation are studied. The UV-induced shift of the selective reflection maximum λmax is shown to depend on the concentration of the nematic component. For low concentrations of ZhK-440, λmax increases, which correlates with the corresponding temperature-induced changes. For higher azoxy nematic concentrations, λmax decreases, regardless of the temperature behavior of the system. To explain the experimental data, a theoretical description is proposed on the basis of the development of molecular models of helical twisting. Good agreement was obtained between calculated and measured values of the UV-induced shift as a function of the azoxy nematic concentration, with two extrema and an inversion point. The extra twisting arises from the cholesteric mesophase-induced orientation of short molecular axes of cis-isomers formed as a result of irradiation.